Hubungan Harapan Ibu pada Gender Bayi dengan Terjadinya Baby Blues Syndrome Primipara di Praktek Bidan Mandiri Fahri Yanti Kisaran Kab. Asahan Sumatera Utara - Dinda Syahputry Syahputry; Dwi Dhea Ananda Hasibuan; Erika Nova Safrina; Dwi Rawati Dongoran; Harauly Lady Lusiana Manalu (Universitas Malahayati, 2023)
ABSTRACT Baby blues syndrome is a condition that is often experienced by mothers who are just ready to give birth where excessive feelings of sadness and anxiety arise. The purpose of this research is to find out whether there is a relationship between the mother's expectations of the baby's gender and the occurrence of baby blues syndrome in primiparous mothers. This type of research used quantitative methods with a correlational design with a cross sectional approach. The population in the study were 38 mothers who were just ready to give birth with a total sample of 38 people. The results of the study found that out of 38 respondents, there were 15 people (55.5%) respondents whose expectations of the baby's gender were not as expected and experienced baby blues in primiparous mothers and mothers who experienced baby blues there were 12 people (50%) respondents who had the same percentage as primiparous mothers who did not experience baby blues, 12 people (50%). The conclusion of this study is that there is a significant relationship between mothers' expectations of the baby's gender and the occurrence of baby blues syndrome with a p-value of 0.037 and there is a significant relationship between primiparous mothers and the occurrence of baby blues syndrome with a p-value of 0.007. It is recommended for postpartum mothers to further increase their knowledge about how to anticipate the occurrence of baby blues syndrome by participating in health education, and playing an active role in asking questions to dig up information about health sciences. Keywords: Postpartum Mother, Baby Blues Syndrome, Primipara, Baby's Gender ABSTRAK Baby blues syndrome merupakan suatu keadaan yang sering di alami oleh ibu yang baru siap melahirkan dimana timbulnya perasaan sedih dan kegelisahan yang berlebihan. Tujuan dari penelitian untuk mengetahui apakah ada hubungan antara harapan ibu pada gender bayi dengan terjadinya baby blues syndrome ibu primipara. Jenis penelitian yang digunakan metode kuantitatif dengan rancangan korelasional pendeketan cross sectional. Populasi dalam penelitian ada 38 orang ibu yang baru siap melahirkan dengan sampel menggunakan total sampling 38 orang. Hasil dari penelitian didapatkan bahwa dari 38 orang responden, terdapat 15 orang (55,5%) responden yang harapan terhadap gender bayi tidak sesuai diharapan dan mengalami baby blues pada ibu dan ibu primipara yang mengalami baby blues ada 12 orang (50%) responden memiliki presentase yang sama dengan ibu primipara yang tidak mengalami baby blues 12 orang (50%). Kesimpulan dari penelitian ini yaitu ada kaitan yang signifikan antara harapan ibu pada gender bayi dengan terjadinya baby blues syndrome dengan nilai p-value 0,037 dan ada kaitan yang signifikan antara ibu primipara dengan terjadinya baby blues syndrome dengan p-value 0,007. Disanrankan pada ibu postpartum agar lebih meningkatkan pengetahuannya tentang cara mengantisipasi jika terjadinya baby blues syndrome dengan cara ikut penyuluhan kesehatan, dan berperan aktif dalam bertanya untuk menggali informasi seputar ilmu kesehatan. Kata Kunci: Ibu Postpartum, Baby Blues Syndrome, Primipara, Gender Bayi